2000
DOI: 10.1111/j.1553-2712.2000.tb01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol on the Geographic Variation of Driver Fatalities in Motor Vehicle Crashes

Abstract: Abstract. Objective: To determine whether the increased risk of dying in a rural vs nonrural motor vehicle crash (MVC) can be attributed to driver demographics, crash characteristics, or police-reported alcohol use. Methods: A retrospective cohort study was conducted, comparing all rural (116,242) and a 20% random sample of nonrural (104,197) Michigan drivers involved in an MVC during [1994][1995][1996]. Data consisted of all police-reported traffic crashes on public roadways. A logistic regression model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…Other studies have reported that differences in the quality of medical care may partly explain this pattern (Baker et al, 1987;Bentham, 1986). Our study and that by Borgialli et al (2000), both in Michigan, indicate that rural-urban differences in MVC mortality could be partially explained by alcohol use. The finding that drivers involved in MVCs in rural areas are more likely to have a positive BAC than those in urban crashes suggests that differences in drinking behavior could be a risk factor for increased MVC mortality.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…Other studies have reported that differences in the quality of medical care may partly explain this pattern (Baker et al, 1987;Bentham, 1986). Our study and that by Borgialli et al (2000), both in Michigan, indicate that rural-urban differences in MVC mortality could be partially explained by alcohol use. The finding that drivers involved in MVCs in rural areas are more likely to have a positive BAC than those in urban crashes suggests that differences in drinking behavior could be a risk factor for increased MVC mortality.…”
Section: Discussioncontrasting
confidence: 37%
“…This suggests that there might be an association between alcohol-related car crashes and rural areas. A previous study in Michigan demonstrated an association between alcohol-related MVC fatality and rural crash location, using the county as the geographic unit and the MSA status of each county for the urban/rural classification (Borgialli et al, 2000). In our study, both counties are MSAs and would have been classified as urban in the previous study.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, crashes in rural areas have a higher casefatality rate and may have different distributions of speeding, alcohol involvement, safety belt use, vehicle types, and crash mechanisms. [15][16][17][18][19][20] We believed that it was important to control for the effects of geographic locale to make valid estimates about the association between the novice age group and various crash and driver variables.…”
Section: Methodsmentioning
confidence: 99%
“…Motor vehicle crashes are the leading cause of death for 15 to 19 year olds in the United States; in fact, 40% of all deaths among US teenagers are the result of motor vehicle crashes. The death rates among these young drivers are 4 to 8 times higher than among older drivers per mile traveled.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Borgialli and colleagues 4 in their article report that alcohol use by drivers in Michigan was, in part, a significant contribution for fatalities in rural crashes. They recommend that prevention efforts to decrease motor vehicle crash mortality must address the issue of alcohol use.…”
Section: Screening and Brief Intervention For Alcoholmentioning
confidence: 99%